Rethinking the Vanguard : aesthetic and political positions in the modernist debate, 1917-1962 - Maerhofer, John W. (Cambridge Scholars Pub., 2009)
How has political revolution figured into the development of avant-garde cultural production? Is the vanguard an antiquated concept or does its influence still resonate in the 21st century? Focusing closely on the convergence of aesthetics and politics that materialized in the early part of the twentieth century, this study offers a re-interpretation of the historical avant-garde from 1917 to 1962, a turbulent period in intellectual history which marked the apex, crisis, and decline of vangua ...